Анализ угроз и опасностей в комьютерных системах на предмет защиты цифровыми реконфигурируемыми устройствами - Коростиль, Ю.М.; Давиденко, А.Н.; Гильгурт, С.Я.; Панченко, М.М. (Моделювання та інформаційні технології, 2010)
The utilization of the programmable logic for the computer security problems is
investigated. A classification of threats and vulnerabilities in computer systems taking
into account the potential of FPGA-based digital equipment when using for solving
security tasks is proposed.